Disease knowledge, medical experience, health-related quality of life and health-care costs among patients with advanced colorectal cancer in China: protocol for a nationwide multicentre survey - Xi Zhang; Yin Liu; You-Lin Qiao; Hui-Fang Xu; Yan-Qin Yu; Yu-Qian Zhao; Shao-Kai Zhang (BMJ Open)
Background Colorectal cancer (CRC) is one of the most common cancers in China. Most patients have developed advanced stage at diagnosis, leading to a low 5-year survival rate. To optimise prevention strategies, we planned a survey to evaluate the disease knowledge, medical experience and health-related quality of life (HRQOL) before and after the treatment of CRC, and healthcare costs among patients with advanced CRC in China.Methods and analysis This is a nationwide, hospital-based, multicentre survey. Nineteen hospitals in seven cities were selected by multistage stratified sampling. Mainland China is divided into seven regions according to the traditional administrative district definition; two cities of each region were selected through simple random sampling, and then one tertiary cancer hospital and one general hospital were selected for each city. More than 4445 patients with CRC in the selected hospitals with stage III or IV will be enrolled in this study. The trained interviewers will collect information through patients’ self-report and/or medical records, including demographics and medical history; knowledge about CRC high-risk factors, screening procedure and treatment methods; medical experience on CRC screening, diagnosis and treatment; HRQOL before and after CRC treatment; and costs of CRC. All data will be input by two independent staff and verified using Epidata V.3.1 software. Data validation plan will be made to guide data checking. All statistical analyses will be conducted using SAS V.9.4 and SPSS V.24.0 software.Ethics and dissemination The study was approved by the ethics committees of Henan Cancer Hospital, the leading participant hospital. Findings of this study will be disseminated through peer-reviewed open-access journals and presented as posters and/or oral sections in national and international conferences. Results will also be popularised to the public via media or the internet.